Wyzwania konkurencyjności a polityka rozwoju regionów w Polsce po jej wejściu do Unii Europejskiej - Winiarski, Bolesław (Challenges of competitiveness and policy of regional Development in Poland After Its Accession to European Union, 2006)
With the reference to settlements of localization theories and Marshall concept of external benefits and to own research, the author describes the challenges to be faced by the Polish economy after Poland’s accession to the area of common European market points the great role of as an adequate orientated regional policy in the field of improving the competitiveness of national economy. In implementing which public policies, in respect to valid European Union’s rules of free competition and restriction of forms of state’s interventions, can actively influence the improvement of enterprises’ environment, localization attractiveness of regions and incentives to investment, and also regulate in an important way forms, extend and quality of external benefits received by enterprises from environment. Using this function of regional policy in a specific conditions in Poland demands depiction of appropriate strategy, including in particular programs of reconstruction and development of agglomeration and metropolitan regions and regional systems of infrastructure. Author argues that polish side should also postulate the implementation of some modifications in regional policy of European Union, from the point of view of concession of superior priorities for regions affected with unemployment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 89-96